A new genus of Podonominae (Diptera: Chironomidae) in Late Eocene Rovno amber from Ukraine - Baranov, Viktor; Andersen, Trond; Perkovsky, Evgeny (Zootaxa, 2014)
The genus Palaeoboreochlus Baranov et Andersen, n. gen. is erected based on P. inornatus Baranov et Andersen, n. sp. described from a male found in Late Eocene Rovno amber. The new genus groups with Boreochlus Edwards in the tribe "Boreochlini".